Improvements in Objectively Measured Activity Behaviors Do Not Correlate With Improvements in Patient-Reported Outcome Measures Following Total Knee Arthroplasty - Frimpong, E.; van der Jagt, D.R.; Mokete, L.; Pietrzak, J.; Kaoje, Y.S.; Smith, Anne; McVeigh, Joanne; Meiring, R.M. (2020)
© 2019 Elsevier Inc. Background: Activity monitors have added a new dimension to our ability to objectively measure physical activity in patients undergoing total knee arthroplasty (TKA). The aim of the study is to assess whether changes in the time spent sitting, standing, and stepping were associated with changes in patient-reported outcome measures (PROMs) before and after TKA. Methods: Valid activPAL data (>3 days) and PROMs were obtained from 49 men and women (mean [SD] age, 62.8 [8.6] years; body mass index, 33.8 [7.1] kg/m2) who underwent primary TKA, before and at 6 weeks or 6 months after surgery. Patient-reported symptoms of pain, stiffness, and knee function were obtained using the Knee injury and Osteoarthritis Outcome Score and Oxford Knee Score questionnaires. Results: Mean (SD) Knee injury and Osteoarthritis Outcome Score (80.1 [16.3] to 41.6 [6.5], P < .001) and Oxford Knee Score (12.0 [9.8] to 17.7 [22.8], P < .001) scores improved 6 months after TKA. Walking time (mean [95% confidence interval]; min/d) increased from before (79 [67-91]) to 6 months after TKA (101 [88-114], P = .006). Standing time (318 [276-360] to 321 [291-352], P = .782) and sitting time (545 [491-599] to 509.0 [459.7-558.3], P = .285) did not change from before to 6 months after TKA. Participants took more steps (2559 [2128-2991] to 3515 [2983-4048] steps/day, P = .001) and accumulated more steps (31 [30-34] to 34 [33-35] steps/min, P < .001) after TKA compared to before. There were no associations between changes in activity behaviors and changes in PROMs (P > .05). Conclusion: Despite improvements in self-reported knee pain and functional ability, these changes do not correlate with improvements in objectively measured light-intensity and sedentary activity behaviors.